Analisis Perbandingan Kualitas Produk, Strategi Promosi Dan Persepsi Konsumen Pada Ponsel Oppo Dan Xiaomi Studi Pada Mahasiswa STIE Bima - Asshidiqi , Achmad Hasbi; Muhajirin; Darmawan, Imam (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This research aims to determine the comparative analysis of product quality, promotional strategies and consumer perceptions on Oppo and Xiaomi cellphones. Study on STIE Bima students as measured by the Independent Samples Test and the population in this study are STIE Bima students who have purchased OPPO and XIAOMI. The sampling technique used a purposive sampling method with a sample size of 60 people. The research results show that: There is no significant difference between product quality and Oppo and Xiaomi cellphones. Study on STIE Bima Students; there is a significant difference between the Promotional Strategy of Oppo and Xiaomi cellphones. Study on STIE Bima Students; There is no significant difference between consumer perceptions of Oppo and Xiaomi cellphones. Study of STIE Bima students.